INVESTIGATION OF TENSILE AND SOIL-GEOTEXTILE INTERFACE STRENGTH OF KENAF WOVEN LIMITED LIFE GEOTEXTILES (LLGS) - S. Artidteang; D. T. Bergado; T. Tanchaisawat; J. Saowapakpiboon (Lowland Technology International, 2012)
Most geotextiles are made from polypropylene or polyester polymers formed into woven and nonwoven fabric. Recently, new type of geotextile called Limited life Geotextiles (LLGs) made of natural fibers are utilized. Natural fibers are renewable fibers that can be sustainable into woven geotextiles for various geotechnical engineering applications. Geotextiles have been widely used to improve short term stability of embankments on soft clay by two functions: tensile reinforcement and as a drainage element. The paper presents the results of experimental investigation from the suitable pattern of woven Kenaf LLGs for soil reinforcement. Three patterns of weaving Kenaf LLGs were obtained, namely: plain, knot-plain, and hexagonal patterns. Tensile strength tests were conducted in warp and weft directions to select the most appropriate pattern for soil reinforcement application. The plain pattern of woven Kenaf LLGs is the most appropriate pattern due to its high tensile strength. Moreover, large scale direct shear tests were carried out to find the interface strength of Kenaf woven LLGs with sand backfill material as well as the sand backfill materials under different normal confining pressures of 40, 80, and 120 kPa. The important variables for LLGs reinforcement structure design and analysis were investigated. Furthermore, pullout tests were performed using normal confining pressures of 20, 40 and 60 kPa which cover the range of possible applied confining pressures in the field applications. Slippage failure occurred below the normal confining pressure of 40 kPa and tensile failure occurred at higher normal confining pressures.